Low hematocrit reduces the efficiency of CD34+ cell collection when using the Spectra Optia continuous mononuclear cell collection procedure. Issue 5 (24th March 2022) - Kondo, Takumi; Fujii, Nobuharu; Fujii, Keiko; Sumii, Yuichi; Urata, Tomohiro; Kimura, Maiko; Matsuda, Masayuki; Ikegawa, Shuntaro; Washio, Kana; Fujiwara, Hideaki; Asada, Noboru; Ennishi, Daisuke; et al.
Abstract: Background: CD34 + cell collection efficiency (CE) is the determining factor when calculating processed blood volume (PBV) for leukapheresis (LP). However, the factors affecting CE in the continuous mononuclear cell collection (cMNC) protocol performed by the Spectra Optia apheresis system are not well established. Study Design and Methods: We retrospectively collected the data from 147 consecutive apheresis procedures across 106 healthy donors and 27 patients completed between July 2016 and December 2020 at the Okayama University Hospital. All procedures were performed using the Optia cMNC protocol. Results: The median CD34 + CE2 was significantly higher in the donor samples (64.3%) than in the patient samples (46.8%) ( p  < .0001). WBC counts, hematocrit, and platelet counts were all significantly higher in the donors than in the patients, and there was a moderate positive correlation between CD34 + CE2 and hematocrit ( r  = .47, p  < .0001), with the equation of the line being y  = 1.23 x  + 12.23. In contrast, there was only a very weak correlation between CD34 + CE2 and WBC or platelet count. In addition, low hematocrit correlated with an increased time to interface formation. Conclusion: These data revealed the negative impact of low hematocrit on the efficiency of CD34 + cell collection when using the Optia cMNC protocol and suggest that hematocrit values should also be considered when determining PBV.